FEATURES OF PROVIDING SOCIAL SERVICES IN RURAL COMMUNITIES - Gunko, Serhii; Liakh, Tetiana; Vainola, Renata; Lekholetova, Maryna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
Given the potential territorial isolation, lack of necessary contacts, and social agencies, the current situation of a state of war highlights the problem of optimizing the provision of social services to vulnerable population groups in rural communities. The aim of this article is to identify and characterize the features of providing social services in a rural community, determining the factors and environmental aspects that influence the content, forms, and methods of providing social services in a rural community. The authors analyze and summarize approaches to defining the concept of "community" and grouping communities based on various characteristics of the social environment. The study identifies problems in rural society that may affect the process, types, and forms of providing social services (relatively high level of societal social control over individuals; limitations in the social integration opportunities of individuals into the social environment; limitations of social status and role positions in the socialization process; high probability of social exclusion; specific division of labor; limited social contacts; a small number of social institutions influencing the socialization process). Throughout the research, the authors emphasize the need to focus social work in rural areas on supporting youth, young families, and youth initiatives. They outline types of social services to emphasize in rural communities, aimed at social prevention, social support, and social services. The study identifies factors influencing the process of providing social services in a rural community (seasonal, socio-historical, socio-pedagogical, socio-cultural, educational, socio-domestic, socio-demographic, socio-ethnic, socio-religious). The authors see promising research directions in determining the satisfaction with the provision of social services in a rural community and identifying conditions for the effectiveness of providing social services in a rural community.